Ovarian cholesterol efflux: ATP-binding cassette transporters and follicular fluid HDL regulate cholesterol content in mouse oocytes. Issue 2 (19th August 2019) - Quiroz, Alonso; Molina, Paz; Santander, Nicolás; Gallardo, Daniel; Rigotti, Attilio; Busso, Dolores
Abstract: High density lipoproteins (HDL) take up cholesterol from peripheral tissues via ABC transporters and deliver it to the liver via scavenger receptor class B type I (SR-B1). HDL are the main lipoproteins present in follicular fluid (FF). They are thought to derive from plasma, but their origin is still controversial. SR-B1 knock-out (KO) mice have provided important evidence linking HDL metabolism and female fertility. These mice have cholesterol-rich circulating HDL and female infertility that can be restored by treating mice with the cholesterol-lowering drug probucol. Ovulated oocytes from SR-B1 KO females are dysfunctional and show excess cholesterol. The mechanisms explaining the contribution of FF HDL to oocyte cholesterol homeostasis are unknown. Here, using quantitation of filipin fluorescence we show that in SR-B1 KO ovaries, cholesterol excess is first observed in immature oocytes in antral follicles. By performing cross-transplant experiments between WT and apolipoprotein A-I deficient (ApoA-I KO) mice, which lack the main protein component of HDL, we provide evidence supporting the plasmatic origin of FF HDL. Also, we demonstrate that probucol treatment in SR-B1 KO females results in lowering of cholesterol content in their oocytes. Incubation of oocytes from SR-B1 KO mice with purified WT HDL reduces their cholesterol content, suggesting that HDL promote efflux of excess cholesterol from oocytes. In agreement with this hypothesis, we identified ABC transporters in oocytes and observed that ABCA1 KO oocytes have excess cholesterol and lower viability than WT oocytes. Abstract : Summary sentence : Follicular fluid HDL and oocyte ABC transporters regulate mouse oocyte cholesterol homeostasis and contribute to female fertility.